The Crisis and Recovery of Criminal Justice in Late Sixteenth-Century France - Hamilton, Tom (The sixteenth century journal, 2024)
This article considers the role of criminal justice in maintaining state authority and social cohesion during a period of crisis. It presents a case study of the Parlement of Paris during the French Wars of Religion (1562-98), particularly in the final phase of the conflict known as the troubles of the League (1584-98). The article analyses a major body of new evidence in sample periods of appeals to the Parlement that contain a total of 2,500 appellants who brought their cases to Paris from across the court's jurisdiction. This evidence demonstrates that, despite the crisis of the civil wars, the magistrates of the Parlement ensured that some provision for criminal justice remained in place. In this light, we might reassess the resilience of criminal justice under the Old Regime and judge it not only by the ideal of absolute monarchy that its advocates misleadingly proclaimed, but rather within the limited resources and systemic constraints that existed at the time.